Letter from Max Bredig to Georg Bredig, May 17, 1938 - Bredig, Max Albert (1938)
Max Albert Bredig (1902-1977) writes to his father, Georg Bredig (1868-1944) about his first easter in America and his new car.
Keywords: Bredig, Max Albert, 1902-1977; McBain, James William, 1882-1953; Bredig, Georg, 1868-1944; Holidays; Ford automobile